2010
DOI: 10.1007/s11127-010-9599-4
|View full text |Cite
|
Sign up to set email alerts
|

Campaign allocations under probabilistic voting

Abstract: Campaign allocations, Probabilistic voting, D72,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Johnston, Hagen and Jamieson (2004) and Shaw (2006) found that in the 2000 and 2004 US presidential elections, both parties concentrated their campaign visits and television ads on the same set of battleground states. Fletcher and Slutsky (2011) show that parties target the media markets that contain the most persuadable voters. Ridout et al Allcott and Gentzkow (2017) show that social media was an important source of information during the 2016 US presidential elections campaign and that most American adults were exposed to at least one piece of fake information on the Internet.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Johnston, Hagen and Jamieson (2004) and Shaw (2006) found that in the 2000 and 2004 US presidential elections, both parties concentrated their campaign visits and television ads on the same set of battleground states. Fletcher and Slutsky (2011) show that parties target the media markets that contain the most persuadable voters. Ridout et al Allcott and Gentzkow (2017) show that social media was an important source of information during the 2016 US presidential elections campaign and that most American adults were exposed to at least one piece of fake information on the Internet.…”
Section: Related Literaturementioning
confidence: 99%
“…In this state, there is only a generic, non-political, advertiser G, whose demand for ads (per consumer) is p G (q). 12 In this state, the equilibrium (denoted with subscript 0) is such that q 0 G = q. State E, instead, captures a situation when elections approach and political candidates look to reach voters.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnston, Hagen and Jamieson (2004) and Shaw (2006) detailed the geographic concentration of campaign resources in presidential elections and found that in the 2000 and 2004 presidential elections, both parties concentrated their campaign visits and television ads on the same set of battleground states. Fletcher and Slutsky (2011) developed a model of targeting political advertising across multiple districts. They argued that the parties will target the media markets that contain the most persuadable voters and used the WAP data to provide evidence that parties do in fact use this strategy.…”
Section: Advertising Strategiesmentioning
confidence: 99%